Teknologi Informasi Memoderasi Pengaruh Pengendalian Intern dan Kompetensi Sumber Daya Manusia Pada Kualitas Laporan Keuangan - Susena, I Nyoman Andi; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 30 No 3 (2020), 2020)
The purpose of this research is to identify whether information technology moderate the impact of internal control and human resources competency in the financial statement quality. The Reseach was done to 28 regional government officials of Badung. The number of samples are 112 peoples. The technique that was used for the analysis is Moderated Regression Anlysis(MRA). The result of the test shows that internal control affects positively and significantly in the financial statement quality. Human resource competence does not affect the financial statement quality. Information technology strengthen the impact of internal control on financial statement qualityand information technology strengthen the impact of human reources competence on the financial statement quality. Keywords: Control; Competence; IT; Financial Statement.